Changes in ecosystem carbon sequestration and influencing factors from a ’Past-Future’ perspective: A case study of the Tarim River - Jia Xu; Ayong Jiao; Mingjiang Deng; Hongbo Ling (Ecological Indicators)
Amid global warming and intensified human activities, the carbon sequestration (CS) capacity of terrestrial ecosystems faces significant pressure. Ecological Water Conveyance (EWC) projects, by altering land use patterns, have become a key approach to addressing this issue. Therefore, the critical question this study aims to solve is how to enhance regional CS by optimizing EWC measures, based on understanding the relationship between land use changes and CS. To address this, we propose an integrated framework that couples the PLUS-InVEST-OPGD models, adopting a ’past-future’ perspective to explore the relationship between CS and land use changes in the context of EWC. The study found that during the historical period (2000–2020), CS in the Tarim River (TR) area exhibited a pattern of ’ first increasing, then stabilizing.’ Between 2000 and 2010, the total CS increased by 3.5 × 10^6 Mg, accompanied by an expansion of forested areas along the riverbanks and within national parks. However, from 2010 to 2020, the total CS increased by only 0.3 × 10^6 Mg, with forested areas along the riverbanks and within national parks remaining relatively stable. Under three future development scenarios—Natural Increase (NIS), Farmland Protection (FPS), and Ecological Protection (EPS)—CS differences between NIS and FPS are minimal at 0.01 × 10^6 Mg, as both continue existing EWC policies without optimization, with NIS following natural growth and FPS prioritizing farmland preservation. In contrast, the EPS, which introduces optimized EWC strategies to limit urban expansion and enhance ecological sustainability, results in a significant CS increase of approximately 1.1 × 10^6 Mg, with farmland areas also expanding. Through single factor and interactive detection analyses, we found that potential evapotranspiration and annual average groundwater depth play crucial roles in vegetation restoration in arid regions, as EWC helps maintain groundwater levels, reducing plant water stress and supporting vegetation growth, while managing evapotranspiration ensures that the water provided through EWC is efficiently utilized for ecosystem recovery and CS. Under the current EWC model and prevailing climate and human activity conditions, the CS capacity of ecosystems appears to stabilize. To further enhance the region’s CS potential, optimizing EWC strategies is essential. It is recommended to construct a ’surface’ water conveyance network through engineering measures, in addition to the existing ’linear conveyance’ model, to improve water resource utilization efficiency. The findings of this study offer valuable insights not only for the TR region but also for other arid inland river basins worldwide, providing a replicable framework for ecological restoration and water management.